Janek191:
x, x q , x q
2
x + x q + x q
2 = 62 ⇒ x*( 1 + q + q
2 ) = 62
log x + log x q + log x q
2 = 3 ⇒ lg (x *x q * x q
2) = 3 ⇒ log x
3 q
3 = 3
| 10 | |
x3 q3 = 103 ⇒ x q = 10 ⇒ x = |
| |
| q | |
zatem
10 + 10 q + 10 q
2 = 62 q
10 q
2 − 52 q + 10 = 0
5 q
2 − 26 q + 5 = 0
Δ = 576
√Δ = 24
| 26 − 24 | | 1 | | 26 + 24 | |
q = |
| = |
| lub q = |
| = 5 |
| 10 | | 5 | | 10 | |
x = 50 lub x = 2
zatem
1) x = 50, x q = 10 , x q
2 = 2 50 + 10 + 2 = 62
lub
2) x = 2 x q = 10 x q
2 = 50 2 + 10 + 50 = 62
Odp: 50, 10, 2 lub 2 , 10, 50.
========================